The use of investigative methods in teaching and learning primary mathematics in Lebowa schools : a case study - Sebela, Mokgoko Petrus (Rhodes University, Faculty of Education, Department of Education, 1999)
This is a report on research conducted in Lebowa (Northern Province) Primary Mathematics Project schools. In view of the high failure rate of matric students, the researcher believes that it is necessary that ways should be devised to improve mathematics understanding from the first level of schooling. A research study was made of constructivist and investigative teaching and learning methods as employed by teachers in a number of primary schools in the area. The researcher believes that investigative and constructivist teaching approaches produce better results than the traditional approach. He further believes that children learn better in a co-operative non-threatening classroom environment. A pilot study was made with two experimental schools and two control schools. The schools were selected from both urban and rural areas. The experimental schools are operating under the PMP and the control schools are not. The experimental schools are also supported by expert teachers called key teachers. Many of these key teachers have attended courses at Leeds University, while others have been trained locally in the theory and practice of constructivist and investigative teaching and learning. Chapter 3 illustrates clearly what is done in the Project schools. The methodology employed in the research included qUestionnaire responses from 174 teachers. Written tests by four schools (350 pupils), and interviews with 55 people, including directors of education, inspectors, principals, teachers and parents. Observations in classes were also done. Another questionnaire was given to 484 pupils. The tests were mitten on two occasions: an initial test was written during November 1993, the second year of the PMP project, while a second test was written the following year. Data collected was analysed and positive results obtained. The results from the tests indicated that pupils in experimental schools where constructivist and investigative approaches are used, perform better than those from schools where the traditional approach is still used. They indicated that children in PMP schools develop a better understanding of mathematics. This would seem to indicate that the constructivist and investigative approach to teaching produces better results than the traditional approaches. The reader will find graphs indicating the results and their analysis in Chapters 4 and 5. It is recommended by the researcher that: - Constructivist and investigative teaching and learning methods be introduced to all schools. - The services of key teachers be supported by the Department - The Department should equip all schools with the necessary materials for proper teaching and learning, or provide materials for schools to make their own teaching aids. - Teachers be involved with materials production where they are given guidance on how teaching aids can be made. - The curriculum for primary school mathematics be revised and changed, especially in view of the fact that at present it does not cater for local needs. It was planned by whites and it caters mainly for those with an European cultural background.
Keywords: Mathematics -- Study and teaching (Primary) -- South Africa -- Northern Province -- Case studies; Mathematics -- Study and teaching (Primary) -- South Africa -- Northern Province